2022
DOI: 10.2478/acb-2022-0002
|View full text |Cite
|
Sign up to set email alerts
|

Silica nanoparticles in targeted human cancer therapy

Abstract: One of the leading causes of death across the world is cancer. Despite massive attempts to develop efficient chemotherapy medications, there is still a significant toxicity and selectivity problem. We are looking for novel therapies and preventative strategies due to the toxicity of contemporary chemotherapy and cancer cell resistance to anticancer drugs. The structure and molecular characteristics of Na2SiO3 nanoparticles were investigated using density-functional theory calculations at the B3LYP/6-311G** lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the laboratory, water samples were placed in containers and exposed to the natural silica physical field for a set amount of time. In the field, the natural silica physical field was created by placing the water source near layers of silica-rich [6].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the laboratory, water samples were placed in containers and exposed to the natural silica physical field for a set amount of time. In the field, the natural silica physical field was created by placing the water source near layers of silica-rich [6].…”
Section: Methodsmentioning
confidence: 99%
“…While previous studies have focused on raising the pH levels of water by adding alkaline compounds, recent research has suggested using baking soda, which has a pH of approximately 9. However, there are several unfavorable health effects associated with adding baking soda to water, including hypokalemia, hypochloremia, high blood salt levels, deterioration of kidney illness, deterioration of heart failure, muscle weakness and spasm, and increased production of stomach acid [6]. Studies also determine that alkaline water reduces acid in the stomach, which helps kill pathogens and bacteria in the stomach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation